(untitled) (BIRDEM Medical Journal, 2025)
Background: A hereditary condition known as hemoglobinopathies causes one of the globin chains of the hemoglobin molecule to have an abnormal structure. Worldwide, inherited hemoglobin abnormalities are common. Studies on thalassemia and hemoglobinopathies are scarce in Bangladesh. Even though this country had not done much research on the subject, the number of people with inherited hemoglobin problems is alarming. This study was conducted to assess the forms of inherited hemoglobin abnormalities among the patients of a tertiary care hospital. Methods: A total of 431 individuals were recruited in this study. The samples were collected from both outdoor and indoor patients of BIRDEM General Hospital, BIRDEM General Hospital (Women and Children), Bangladesh Institute of Health Sciences (BIHS) from January to June 2024. The patients were referred to these hospitals from different regions of the country. The blood samples collected from them were analyzed at the Department of Laboratory Medicine, BIRDEM General Hospital Dhaka. Results: Out of 423 cases, 268 (63.3%) blood samples showed normal findings and 155 (36.7%) blood samples showed different forms of haemoglobinopathies in hemoglobin electrophoresis. Out of 155 abnormal cases, 58 (37.4%) were males and 97 (62.6%) were females. The most common form was HbE trait (20.09%) followed by â-thalassemia trait (13.71%). Moreover HbE disease was found in 0.95%, Hb D Punjab trait 0.95%, E-b -thalassemia in 0.47%, b-thalassemia major in 0.47%. Conclusion: It is expected that public health officials will find the current data useful in adjusting current facilities to lower the number of thalassemia carriers and haemoglobinopathies in Bangladesh. BIRDEM Med J 2025; 15(3): 131-135